Methods to Assess Social Comparison Processes Within Persons in Daily Life: A Scoping Review - Arigo, Danielle; Mogle, Jacqueline A.; Brown, Megan M.; Pasko, Kristen; Travers, Laura; Sweeder, Logan; Smyth, Joshua M. (Frontiers in Psychology, 2020)
Self-evaluations relative to others (i.e., social comparisons) have well-established implications for health and well-being, and are typically assessed via global, retrospective self-report. Yet, comparison is inherently a dynamic, within-person process; comparisons occur at different times, on a range of dimensions, with consequences that can vary by context. Global, retrospective assessment forces aggregation across contexts and reduces ecological validity, limiting its utility for informing a nuanced understanding of comparisons in daily life. Research across social and clinical psychology has implemented methods to assess comparisons naturalistically, involving intensive, repeated assessments of comparison occurrence, characteristics, and consequences in everyday life (via ecological momentary assessment or daily diaries). Although promising, this work to date lacks an overarching conceptual framework for guiding decisions about assessment design and implementation. To address this gap, the aims of this scoping review were: (1) to summarize available literature on within-person naturalistic assessment of social comparison, and (2) to provide a set of key considerations to inform future social comparison research using within-person naturalistic assessment. Searches in PubMed, PsycInfo, and CINAHL identified relevant articles published before June 2019. Articles were included if they described at least 3 comparison assessments within each participant, taken in the natural environment, and spaced no more than ~24 hours apart (i.e., repeated momentary or daily assessment). In articles meeting these criteria (33 unique studies across 36 published papers), we summarized aspects of the comparison assessment, including recording methods, direction (e.g., upward, downward), target (e.g., friend, stranger), and dimension (e.g., status, appearance). Most studies assessed appearance comparisons (vs. other comparison dimensions) and collected information in response to signals (rather than initiated by participants). However, there was considerable heterogeneity in the number of assessments, assessment periods, recording modalities, and comparison predictors and outcomes assessed. Findings broadly establish heterogeneity in the aspects of comparison considered critical for within-person naturalistic assessment. We describe key decision points for future work to help advance within-person naturalistic assessment methods and improve the utility of such approaches to inform research, theory, and intervention.